2020
DOI: 10.1002/jsfa.10636
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of green and red perilla to LED‐based light

Abstract: BACKGROUND Light‐emitting diodes (LEDs) are widely used in closed‐type plant production systems to improve biomass and accumulate bioactive compounds in plants. Perilla has been commonly used as herbal medicine because of its health‐promoting effects. This study aimed to investigate the physiological and biochemical responses of green and red perilla under various visible‐light spectra. RESULTS Results showed that red (R) LEDs improved fresh weights of shoots and roots, plant height, internode length, node num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
(79 reference statements)
1
12
0
Order By: Relevance
“…Therefore, the spectral wavelengths and their ratios in the light sources mainly caused the variations in individual compound accumulation. The RB treatment significantly enhanced the contents of most phenolic acids (i.e., protocatechuic, chlorogenic, gallic, ferulic, veratric, and benzoic acids) and flavonols (i.e., catechin, epicatechin, epigallocatechin gallate, rutin, catechin gallate, and naringin) in both cultivars, which is consistent with the results of numerous studies that have demonstrated the effectiveness of R and B lights alone or in combination in stimulating the production of plant secondary metabolites [40][41][42]. B light has generally been reported to be more effective in increasing the biochemical compounds in plants because of the involvement of its photoreceptor (cryptochrome) in the accumulation of phenolic acids and flavonoids [43].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the spectral wavelengths and their ratios in the light sources mainly caused the variations in individual compound accumulation. The RB treatment significantly enhanced the contents of most phenolic acids (i.e., protocatechuic, chlorogenic, gallic, ferulic, veratric, and benzoic acids) and flavonols (i.e., catechin, epicatechin, epigallocatechin gallate, rutin, catechin gallate, and naringin) in both cultivars, which is consistent with the results of numerous studies that have demonstrated the effectiveness of R and B lights alone or in combination in stimulating the production of plant secondary metabolites [40][41][42]. B light has generally been reported to be more effective in increasing the biochemical compounds in plants because of the involvement of its photoreceptor (cryptochrome) in the accumulation of phenolic acids and flavonoids [43].…”
Section: Discussionsupporting
confidence: 89%
“…B light has generally been reported to be more effective in increasing the biochemical compounds in plants because of the involvement of its photoreceptor (cryptochrome) in the accumulation of phenolic acids and flavonoids [43]. Meanwhile, the role of R light or combined RB light in biochemical accumulation depends on plant species and cultivars [9,42]. Son et al also reported that a higher proportion of B in combined RB light increased total phenolic acid and flavonoid contents as well as the antioxidant capacity of red and green leaf lettuce [35], whereas the same green leafy variety of lettuce grown under R light was confirmed to demonstrate a relative inefficiency in modifying total phenolic acid and flavonoid contents [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported increased TPC in Chinese cabbage and lettuce irradiated with blue LEDs alone compared with those irradiated with red LEDs alone or a combination of red and blue LEDs [ 98 ], indicating that the effects of LEDs on TPC varied among plant species. Several studies have investigated the levels of phenolic compounds in plant species grown under LED irradiation [ 55 , 57 , 58 , 68 , 72 , 174 , 175 ]. Chung et al [ 4 ] reported an increase in malonyldaidzin, malonyl genistin, salicylic acid, p -hydrobenzoic acid, and gentisic acid levels in Pachyrhizus erosus grown under red LED irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…RA, CA and PA were analyzed using an HPLC system (YL9100; Young Lin Instrument, Anyang, Republic of Korea). The whole process for the extraction of samples and analysis of these compounds has been described in a previous study (16). The content of each compound was expressed as milligrams of the respective standard per gram DW (mg g −1 ).…”
Section: Methodsmentioning
confidence: 99%